Rare implant-specific complications of the MoPyC radial head prosthesis - Hackl, Michael; Wegmann, Kilian; Koslowsky, Thomas Christian; Zeifang, Felix; Schoierer, Oliver (Journal of shoulder and elbow surgery, 2017)
Background: According to currently available data, the clinical short-term results of the MoPyC radial head prosthesis (Bioprofile, Tornier, Montbonnot-Saint-Martin, France) seem favorable. However, we have encountered several implant-specific complications in recent years. Hence, this case series reports rare complications after radial head arthroplasty with the MoPyC prosthesis to make surgeons aware of their existence and to provide information about the underlying cause and possible salvage strategies. Methods: A retrospective chart review from 2011 to 2016 was conducted to identify all adult patients with a minimum 2-year follow-up who underwent or were referred after radial head arthroplasty with the MoPyC radial head prosthesis and experienced implant-related complications. Results: Five patients with 7 implant-related complications were found. One patient experienced breakage of the pyrocarbon head. In another patient, breakage of the stem and—after revision surgery—partial breakage were observed. Disassembly of the prosthesis was seen in 1 case. Extensive periprosthetic stress shielding was seen in 3 patients resulting in symptomatic loosening (1), periprosthetic radial neck fracture (1), and stem migration (1). Conclusions: Whereas clinical short-term results of the MoPyC radial head prosthesis are satisfactory, rare implant-related complications can occur. Surgeons should be aware of these complications as they may lead to a poor outcome.